Książki jako ofiary rewolucji. Konsekwencje powstania i upadku NRD dla literatury i księgarstwa - Okoński, Krzysztof (Acta Universitatis Lodziensis. Folia Librorum, 2013)
This article analyses most important phenomena, events and trends connected with the history of literature and readership at the time of the German Democratic Republic and after 1990 in the eastern part of Germany. The political system of the state ruled by W. Ulbricht and E. Honecker demonstrated a number of typical solutions of communist cultural policy, yet the literary life and book market resulted from the division of Germany and other specific circumstances (e.g., the Berlin Wall, Nazi dictatorship before 1945, book burning 1933, more intense Stalinist trends as well as abundant traditions of bookselling). The article also focuses on manifestations of the protest culture such as as Samisdat, Tamisdat, the activity of ecological libraries as well as initiatives aiming at saving independent publications from the GDR period.This article analyses most important phenomena, events and trends connected with the history of literature and readership at the time of the German Democratic Republic and after 1990 in the eastern part of Germany. The political system of the state ruled by W. Ulbricht and E. Honecker demonstrated a number of typical solutions of communist cultural policy, yet the literary life and book market resulted from the division of Germany and other specific circumstances (e.g., the Berlin Wall, Nazi dictatorship before 1945, book burning 1933, more intense Stalinist trends as well as abundant traditions of bookselling). The article also focuses on manifestations of the protest culture such as as Samisdat, Tamisdat, the activity of ecological libraries as well as initiatives aiming at saving independent publications from the GDR period.